Reviews and Responses for Investigation of Point Merge Utilization Worldwide Using Opensky Network Data - Li, Max; Mori, Ryota; Spinielli, Enrico; Hardell, Henrik; Polishchuk, Tatiana; Smetanová, Lucie (Journal of Open Aviation Science, 2024)
See detailed reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2023.7218